Troponin I Level and cardiac outcomes in patients with unstable angina and non-ST-elevated myocardial infaction admitted in NICVD, Dhaka, Bangladesh (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13244 J. Dhaka Med. Coll. 2012; 21(1): 83-87